UCHL1 Regulates Lipid and Perilipin 2 Level in Skeletal Muscle - Antony, Ryan; Aby, Katherine; Gao, Hongbo; Eichholz, Mary; Srinivasan, Rekha; Li, Yifan (Frontiers in Physiology, 2022)
Ubiquitin C-terminal hydrolase L1 (UCHL1) is a deubiquitinating enzyme that was originally found in neurons. We found that UCHL1 is highly expressed in slow oxidative skeletal muscles, but its functions remain to be fully understood. In this study, we observed that UCHL1 protein levels in skeletal muscle and C2C12 myotube were downregulated by fasting or glucose starvation respectively. Skeletal muscle selective knockout (smKO) of UCHL1 resulted in a significant reduction of lipid content in skeletal muscle and improved glucose tolerance. UCHL1 smKO did not significantly change the levels of key proteins involved in oxidative metabolism such as SDHA, Akt, or PDH. Interestingly, while the levels of the major lipases and lipid transporters were unchanged, perilipin 2 was significantly downregulated in UCHL1 smKO muscle. Consistently, in C2C12 myotubes, UCHL1 siRNA knockdown also reduced perilipin 2 protein level. This data suggests that UCHL1 may stabilize perilipin 2 and thus lipid storage in skeletal muscle.